Modelo de gestión por competencias para mejorar el desempeño laboral de la empresa “Explocen C.A” ubicada en la ciudad de Latacunga en el km 2 1/2 vía Saquisilí-Poaló en el periodo 2015-2016 - Moreno Flores, Katherine Victoria (2016)
The research focused in a design of a competence management model to improve the job performance at "EXPLOCEN CA" company, this was raised considering the need for the company to raise the performance of its employees in different work positions. For the development of the thesis a number of tools in order to identify the problems faced by the company, so that a FODA diagnostic was used, which could detail both positive and negative aspects of both internal and external, currently EXPLOCEN is facing, getting as a that the main problem is poor management that is given to human talent. Based on research, methods….